Latent-Path Modeling Dengan Partial Least Square Guna Memprediksi Pengaruh Faktor-Faktor Isu Lingkungan Terhadap Sistem Pengendalian Manajemen Lingkungan - F.X. Kurniawan Tjakrawala; Gregorius Arvan (Jurnal Ekonomi dan Bisnis, 2015)
This study explored the recently topic of environmental management control system issue which has't been conducted by Indonesian's researcher in accounting. The purpose of this study is to predict the effect of perceived factors related to environmental issues such as perceived ecological uncertainty; the degree of environmental proactivity; and stakeholders pressure that affected environmental management control systems. Primary data collection through survey method was done by distributing 325 sets of questionnaires and addressed to the managerial level of respondents who work in the ten of manufacturing companies listed on IDX, with the response rate of 19,70 percent. This study implements a latent-path modeling. Due to relatively few sample (N=64), this study did not allow covariancebased SEM to be applied in testing the hypotheses. So then the three hypotheses of this study were tested by the technique of partial least squares (PLS) using SmartPLS v.2 package, which applied the component-based SEM approach. The hypotheses test were empirically proved the ability to predict that all of these environmental issues positively influenced the environmental management control systems significantly. In the future, similar study still probably to be developed (in Indonesia) based on covariance-based SEM to gain the clear theoretical confirmation.